Wpływ antropopresji na stan ekologiczny małej zlewni rzecznej na przykładzie Strugi Młyńskiej = Influence of human impact on the ecological condition of small catchment area on the example of Struga Młyńska - Dawid Aleksander Szatten (Kazimierz Wielki University, 2015)
Szatten Dawid. Wpływ antropopresji na stan ekologiczny małej zlewni rzecznej na przykładzie Strugi Młyńskiej = Influence of human impact on the ecological condition of small catchment area on the example of Struga Młyńska. Journal of Education, Health and Sport. 2015;5(5):401-412. ISSN 2391-8306. DOI 10.5281/zenodo.17905 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A401-412 https://pbn.nauka.gov.pl/works/561551 http://dx.doi.org/10.5281/zenodo.17905 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.03.2015. Revised 18.04.2015. Accepted: 24.05.2015. Wpływ antropopresji na stan ekologiczny małej zlewni rzecznej na przykładzie Strugi Młyńskiej   Influence of human impact on the ecological condition of small catchment area on the example of Struga Młyńska   Dawid Szatten   Uniwersytet Kazimierza Wielkiego w Bydgoszczy, Wydział Kultury Fizycznej, Zdrowia i Turystyki, Instytut Geografii, 85-428 Bydgoszcz, ul. Mińska 15   Streszczenie Zlewnia Strugi Młyńskiej cechuje się dużym wpływem antropopresji. Wynika to z jej położenia w bezpośrednim sąsiedztwie miasta Bydgoszczy oraz stosunkowo małej powierzchni zlewni całkowitej. Decydujący wpływ na jakość wód mają punktowe źródła zanieczyszczeń oraz presja obszarów zurbanizowanych. Mimo korzystnego pokrycia terenu zlewni (lasy), odnotowuje się znaczący dopływ substancji autochtonicznej ze obszaru zlewni. W takim przypadku wykonanie waloryzacji przyrodniczej wykazuje duże zróżnicowanie wewnętrzne środowiska na stosunkowo małej przestrzeni.   Abstract The catchment area of Struga Młyńska is characterized by strong anthropopression impact. This is due to its location in the immediate vicinity of the city of Bydgoszcz and the relatively small area of the catchment. The main impact on the water quality have point sources of pollution and pressure from urban areas. Despite beneficial cover of catchment land (forests) there has been noticed a significant influx of autochthonous substances from the catchment area. In this case, the execution of natural valorisation has high internal diversity of the environment in a relatively small area of catchment.   Słowa kluczowe antropopresja, punktowe źródła zanieczyszczeń, jakość wód, waloryzacja przyrodnicza.   Key words anthropopression, point sources of pollution, water quality, natural valorisation.